2018
DOI: 10.1136/heartjnl-2018-313089
|View full text |Cite
|
Sign up to set email alerts
|

Effects of supplemental oxygen therapy in patients with suspected acute myocardial infarction: a meta-analysis of randomised clinical trials

Abstract: Although supplemental O therapy is commonly used, it was not associated with important clinical benefits. These findings from eight RCTs support departing from the usual practice of administering oxygen in normoxaemic patients.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

3
32
0
3

Year Published

2019
2019
2023
2023

Publication Types

Select...
7
1
1

Relationship

2
7

Authors

Journals

citations
Cited by 39 publications
(38 citation statements)
references
References 37 publications
3
32
0
3
Order By: Relevance
“…When focusing on patients with ST-elevation MI, they found a similar result (9). Two meta-analyses of oxygen therapy in patients with acute MI reached the same conclusions, which were that oxygen therapy was not associated with important clinical outcomes in normoxemic patients (10,11). Greater cardiac injury did not lead to more death in patients with acute MI.…”
Section: Discussionmentioning
confidence: 75%
“…When focusing on patients with ST-elevation MI, they found a similar result (9). Two meta-analyses of oxygen therapy in patients with acute MI reached the same conclusions, which were that oxygen therapy was not associated with important clinical outcomes in normoxemic patients (10,11). Greater cardiac injury did not lead to more death in patients with acute MI.…”
Section: Discussionmentioning
confidence: 75%
“…However, thrombolytic therapy or coronary intervention can trigger myocardial ischemia reperfusion [2,3]. Myocardial ischemia reperfusion can further aggravate the original myocardial injury, and this pathological process is clinically known as myocardial ischemia reperfusion injury (MIRI) [4]. Current studies have shown that the case mechanism of MIRI is very complex, which is closely related to increased myocardial oxidative stress after MIRI, myocardial apoptosis caused by Ca overload, or decreased stability of mitochondrial membrane, autophagy, myocardial inflammation, and energy metabolism disorder [5,6].…”
Section: Introductionmentioning
confidence: 99%
“…These findings were confirmed in a recent metaanalysis including eight RCTs studying the effects of supplemental O 2 therapy in patients with suspected and confirmed MI (n = 7998), showing no clinical benefits [45]. In another meta-analysis including 25 RCTs and a total study population of 16,037 acutely ill patients, it was shown that supplemental O 2 therapy in normoxemic (blood O 2 saturation ≥ 94%) patients increased mortality [46].…”
Section: Discussionmentioning
confidence: 76%